Editorial Introduction - Catherine F. Compton-Lilly (Networks: An Online Journal for Teacher Research, 2007)
While Networks has always been an online journal, in the past year, with the help of a dedicated and patient staff at my university, we can now manage the entire review and publication process online. The new system affects the ways prospective authors submit papers to the journal.